Expressing dynamic XML inclusion dependencies - Wahid, Norfaradilla; Kasim, Shahreen (American Scientific Publishers, 2018)
XML has been widely accepted as a promising web data storage format. Researches of expressing integrity constraints in the XML have become important as the needs of using this data format increased. This paper will discuss the Inclusion Dependencies that is one of important integrity constraints, especially in a static environment of databases. In some conditions, it is essential to handle unique constraints, which involve dynamic features, i.e., the transition properties between consecutive states in a database. In this paper, we describe the notion of dynamic Inclusion Dependencies for XML (DXINDs). We give the definition of DXINDs and propose to express the constraints on top of existing XML schema using the Schematron.